Intrauterine Vertical Transmission of SARS-CoV-2 Infection Among Confirmed Cases of Pregnant Women: "A Double Burden for the Pregnant Women"-A Systematic Review - Addisu Dabi Wake (SAGE Publishing, 2022)
Introduction . The world health organization (WHO) has declared the outbreak of novel coronavirus (2019-nCoV), which is now known as Coronavirus Disease 2019 (COVID-19). Whereas, its quick global spread has resulted in a worldwide pandemic. The present review article was intended to evaluate intrauterine vertical transmission of SARS-CoV-2 infection among confirmed cases of pregnant women. Methods . Web of Science, EMBASE, PubMed, African Journals OnLine, Scopus, PsycINFO, HINARI, Cochrane Library, Wiley Online Library, and Google scholar were used for search. Result . A total of 43 articles were included in to this systematic review. A total of 1,300 neonates born from pregnant women confirmed for COVI-19 were tested for SARS-CoV-2 infection by real-time reverse transcriptase-polymerase chain reaction (RT-PCR). From the 1,300 neonates tested for SARS-CoV-2 infection, 93 neonates were found positive for this infection by RT-PCR. From this systematic review finding, the vertical transmission rate of SARS-CoV-2 infection was 7.15%. This pandemic has stressed the entire public, particularly pregnant women and healthcare providers, while it challenged antenatal care and postnatal care by far. Thus, even being under lockdown in the middle of a global pandemic is stressful enough. Therefore, imagine the added burden of being pregnant, which could be a double burden for these women. Conclusion . There is no concrete evidence of vertical transmission of SARS-CoV-2. Therefore, due to the limited number of clinical evidences, obstetricians, pediatricians, and other healthcare providers should continuously update their knowledge and be conscious about the transmission of SARS-CoV-2 vertically during pregnancy.